Assessing discrepancies between previous plate kinematic models of Mesozoic Iberia and their constraints. Issue 8 (12th August 2016) - Barnett‐Moore, N.; Hosseinpour, M.; Maus, S.
Abstract: Currently, there are several published end‐member plate models that describe the evolution of Iberia during the Mesozoic. We review key geological and geophysical data sets previously used as constraints on these models including (1) geological interpretations of Pyrenean geology; (2) end‐member interpretations of magnetic anomalies along the West Iberian and Newfoundland margins and Bay of Biscay; (3) the paleomagnetic data set of Iberia; and (4) seismic tomography models, which have previously been used to support Cretaceous subduction between Iberia and Eurasia. From this review we identify key constraints and argue that a reasonable plate kinematic model of Iberia should satisfy all of these. Instead, we determine inconsistencies between these key constraints and several published end‐member plate models through a kinematic analysis using the GPlates software. We also analyze published seismic tomography models, not previously considered, across northern Africa and Iberia, and identify no slab preserved within the mantle supposedly linked to Cretaceous subduction between Iberia and Eurasia. A lack of published geological evidence along the Pyrenees supporting this subduction history also casts doubt on this scenario. Our kinematic analysis highlights that, first, the cessation in transtensional motion between Iberia and Eurasia by the Albian cannot be kinematically reconciled with the concurrent breakup between Iberia and Newfoundland in the Atlantic when reconstructing existing continent‐ocean boundary interpretations along their respective margins. Second, either fit of the contentious end‐member M 0 interpretations (~120.6 Ma) between Iberia and Newfoundland implies plate velocities of Iberia that results in its undocumented transpressional or compressional motion relative to Eurasia until C 34 . Key Points: We identify discrepancies between kinematic constraints on Mesozoic Iberia from the Atlantic and Pyrenees We identify kinematic inconsistencies between several previous end‐member reconstructions of Mesozoic Iberia An analysis of global seismic tomography in the region does not support Cretaceous subduction between Iberia and Eurasia